The Emotional Impact of Influencer Fatigue on Online Shopping Decisions - Fitriani, Salma (Journal of Sustainability Industrial Engineering and Management System, 2025)
This study investigates the emotional impact of influencer fatigue on online shopping decisions by employing a qualitative research approach based on systematic literature analysis. The objective is to understand how the saturation of influencer content affects consumer trust, emotional engagement, and purchasing behavior in digital platforms. The research draws on an extensive review of 50 peer-reviewed articles published between 2018 and 2025, selected through major academic databases such as Scopus, Web of Science, and Google Scholar. Thematic synthesis was used to analyze the literature, enabling the identification of key emotional constructs such as affective exhaustion, parasocial disappointment, trust erosion, and consumer resistance. The findings reveal that influencer fatigue is not merely the result of excessive exposure but a nuanced emotional phenomenon that weakens the persuasive power of social media influencers by triggering psychological disengagement and moral skepticism. Furthermore, this emotional dissonance reduces consumer receptivity to promotional messages and shifts their shopping behavior toward more autonomous and skeptical decision-making patterns. The study also identifies emerging behavioral trends such as de-influencing and digital minimalism as coping strategies adopted by consumers in response to fatigue. From a theoretical perspective, the research advances the conceptualization of influencer fatigue by integrating emotional regulation theory with parasocial interaction and advertising skepticism. From a managerial standpoint, the study suggests that brands and digital marketers must recalibrate their influencer strategies to prioritize emotional sustainability and content authenticity. These findings offer a foundation for further empirical inquiry and guide ethical practices in digital consumer engagement.